Analyses of urogenital Mycoplasma hominis and Ureaplasma urealyticum infections and drug sensitivity in 296 patients - CHEN Junwei; HUANG Sheng; QIU Wei; XIAO Yupeng (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To analyze urogenital Mycoplasma hominis (Mh) and Ureaplasma urealyticum (Uu) infections and drug sensitivity, providing a rationale for choosing antibiotics in clinical practice. [Methods] Clinical data were collected from 296 patients with Mycoplasma infections who visited the First Hospital of Putian City from September 2022 to August 2023. The patients′age, gender and the clinical symptoms were analyzed. Urogenital specimen from patients was cultured for isolation and identification of Uu and Mh. [Results] Among 256 women and 40 men with mycoplasma infections, patients aged 31~40 years old accounted for 40.54%. The rate of Mycoplasma infections did not differ significantly between males and femlaes among all age groups (all P>0.05). Over 55% of the patients with Mycoplasma infections had clinical symptoms (χ2=5.68, P<0.05 vs. no symptoms). Patients with Uu and Mh infections were 238 cases (80.41%) and 5 cases (1.69%), respectively. Fifty-three cases (17.91%) were infected with both Mh+Uu. The positive rates of Uu and Uu+Mh infections were significantly higher in female patients than in male patients (χ2Uu=11.27, χ2Uu+Mh=10.09, P<0.05). In Mh positive patients, Mh was sensitive to both doxycycline and minocycline with a sensitive rate of 100%, but resistant to erythromycin and ciprofloxacin. In Mh+Uu positive patients, the sensitivity rates of doxycycline, minocycline and josamycin were over 90%, but resistant to erythromycin. In Uu positive patients, the sensitivity rates of doxycycline and minocycline were 100% and 99.58%, respectively, and the resistance rate of ciprofloxacin was 76.90%. [Conclusions] Females are more likely to have urogenital tract mycoplasma infections than males, and Uu is the main pathogen. The three types of infections are sensitive to doxycycline and minocycline. In clinical practice, the choosing antimicrobial drugs should be based on the type of infection and the sensitivity to the drugs.